Expert System Utilizing Bayesian Theorem Method for Hernia Disease - Santoso, Budi (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
A hernia is the protrusion of an organ or tissue through an abnormal opening. It occurs when the contents of a cavity protrude through a defect (weak channel) or a weak part of the corresponding cavity wall. In children, hernias usually occur in one of two places: around the navel or in the groin or scrotum area. Reckless handling of hernia, especially in cases of umbilical hernia in children, can lead to serious problems, even death. Therefore, accurate information is crucial in managing hernia in children, and it can be facilitated by an expert system application using the Bayesian Theorem method. The Bayesian Theorem is a theorem commonly used to calculate probabilities for a specific hypothesis. It serves as the basis for Bayesian statistics, with applications in microeconomics, science, game theory, and medicine. Research findings conclude that the expert system built is highly beneficial in expediting early treatment of hernia in children. The developed expert system application is dynamic in determining symptoms, weights, and solutions, allowing for customization. The Bayesian Theorem method proves to be suitable for swift and accurate implementation in diagnosing and treating hernia in children. The accuracy level of the testing results using the Bayesian Theorem method is 100%.